A NOTE ON PARTIALLY ORDERED FUZZY METRIC SPACE VIA COUPLED COINCIDENCE POINTS - Jain, Dr. Arihant; Supekar, Vaijayanti (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we prove a coupled coincidence point theorem in partially ordered fuzzy metric space using Ï•-contractive condition.